Advocates Role in Assistance of the Affected Using Sharp Weapons and Abusing - Agus Ekhsan; Umar Ma'ruf (Law Development Journal, 2020)
Advocate profession is a form of respectable profession (Officium Nobile). The basis for the existence of an Advocate Institute (Legal Advisor) in Indonesia is Act No. 18 of 2003 concerning Advocates. Advocate Assistance is a process of providing ease of solving problems in facing legal processes from clients. The purpose of this research is to know and analyze prosecution procedures, to know and analyze the role of Advocates in the implementation of assistance to the accused and to find out and analyze the factors inhibiting the role of Advocates in the implementation of assistance to the accused of using a sharp weapon and persecution and how to overcome them in the Criminal Case Decision Number: 18/Pid.B/2020/PN Pti. This research uses type research empirical juridical approach, descriptive research specifications. The data used in this study are primary data obtained from field studies which are analyzed qualitatively using law enforcement and justice theories. Then for secondary data obtained from material documents or library materials. Research result conclude that The role of advocates in assisting the accused of using a sharp weapon and maltreatment on behalf of Danang Purwanto bin Parmuji against the verdict of case Number: 18/Pid.B/2020/PN Pti has been maximized with the existence of the right of the defendant's legal counsel to file a defense (Pledoi) of the public prosecutor's criminal charges, presenting a witness who defended the defendant, so that the verdict The Panel of Judges sentenced the defendant to a prison sentence of 4 (four) months and 15 (fifteen) days. It is hoped that in the future there must be moral values and justice for the creation of a common understanding of the law and according to the laws and regulations to achieve a fair legal process in society.